QUALITY OF ELECTRONIC MANUFACTURING SERVICE IDENTITY CARD AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION TOJO UNA-UNA DISTRICT - Rahmadani A Tobeki, Safitri; Nawawi, Muh.; Nasrullah, Nasrullah (CV. Lafadz Jaya, 2024)
In general, this study aims to determine the Quality of Service in Making E-KTP at the Population and Civil Registration Office of Tojo Una-Una Regency. In its implementation, this study uses a descriptive method, namely a method that is compiled based on certain rules in a real context, which aims to describe and explain systematically and accurately about the state of the quality of E-KTP making services at the agency. This study is based on a qualitative approach. The theory used refers to the concept put forward by Zaithaml, Pasuraman, and Berry, as quoted by Pasolong (2007:135), which includes 5 (five) main indicators, namely: physical appearance, reliability, responsiveness, assurance and empathy. The results of this study indicate that the Quality of E-KTP Making Services at the Population and Civil Registration Office of Tojo Una-Una Regency, it can be concluded that of the 5 (five) aspects assessed, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy, 3 (three) aspects have been running optimally, namely Tangible, Reliability, and Responsiveness. While 2 (two) aspects that have not run optimally, namely Assurance and Empathy are not running optimally. It is considered not optimal because there are still some employees who show discriminatory actions in providing services to the community.